2018
DOI: 10.1105/tpc.18.00535
|View full text |Cite
|
Sign up to set email alerts
|

Iron- and Reactive Oxygen Species-Dependent Ferroptotic Cell Death in Rice-Magnaporthe oryzae Interactions

Abstract: Hypersensitive response (HR) cell death is the most effective plant immune response restricting fungal pathogen invasion. Here, we report that incompatible rice (Oryza sativa) Magnaporthe oryzae interactions induce iron-and reactive oxygen species (ROS)-dependent ferroptotic cell death in rice cells. Ferric ions and ROS (i.e., H 2 O 2 ) accumulated in tissues undergoing HR cell death of rice leaf sheath tissues during avirulent M. oryzae infection. By contrast, iron did not accumulate in rice cells during viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
231
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(234 citation statements)
references
References 98 publications
3
231
0
Order By: Relevance
“…3c). Altogether, these results indicate that cyanobacterial cells exposed to a 50°C-undergo an oxidative, iron-dependent form of cell death remarkably similar to ferroptosis in eukaryotic cells (Dixon et al, 2012;Distéfano et al, 2017;Bogacz and Krauth-Siegel, 2018;Dangol et al, 2018).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…3c). Altogether, these results indicate that cyanobacterial cells exposed to a 50°C-undergo an oxidative, iron-dependent form of cell death remarkably similar to ferroptosis in eukaryotic cells (Dixon et al, 2012;Distéfano et al, 2017;Bogacz and Krauth-Siegel, 2018;Dangol et al, 2018).…”
mentioning
confidence: 67%
“…Similarly, ferroptosis in plants is characterized by the early depletion of GSH and AsA (Distéfano et al, 2017). In addition, GSH depletion is required for erastin-induced hypersensitive response in rice-Magnaporthe oryzae interaction (Dangol et al, 2018). Synechocystis presents both compounds in different proportions (Suginaka et al, 1999).…”
Section: °C-heat Shock In Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Since ROS production and regulated cell death are reported to be involved in host resistance to M. oryzae infection (Dangol et al ., 2019), we were also interested in assessing the consequences of ferroptosis induction in a blast-susceptible rice cultivar. Towards this goal, we applied RSL3 or erastin, the two ferroptosis inducers that do not affect conidial cell death (Figs 6a,b, S1i), at 22 hpi to the blast-sensitive CO39 rice sheath inoculated with the wild-type M. oryzae isolate, and examined the fungal hyphal development therein.…”
Section: Resultsmentioning
confidence: 99%
“…When M. oryzae interacts with a blast-resistant rice cultivar (termed incompatible interaction), the host immune response, hypersensitive response (HR) cell death in particular, is extremely strong, and blocks M. oryzae from invading the host and thus stops the establishment of blast disease (Liu et al ., 2014). In a seminal study, ferroptotic cell death was reported to be involved in the HR response in the presence of ROS-generating NADP-malic enzyme 2 during incompatible rice- M. oryzae interaction (Dangol et al ., 2019), although further experiments specifically focusing on the rice side are required to validate these findings. Considering the general requirement of ROS production to rice immunity and the universal occurrence of ferroptosis in diverse biological contexts (Distéfano et al ., 2017; Stockwell et al ., 2017; Conrad et al ., 2018; Dangol et al ., 2019), it is interesting to test whether ferroptosis is generally involved in rice defense against M. oryzae infection, in particular whether inducing ferroptosis in susceptible rice can switch on its resistance against the invading pathogen.…”
Section: Introductionmentioning
confidence: 99%